Integrative studies implicate matrix metalloproteinase‐12 as a culprit gene for large‐artery atherosclerotic stroke. (28th August 2017) - Mahdessian, H.; Perisic Matic, L.; Lengquist, M.; Gertow, K.; Sennblad, B.; Baldassarre, D.; Veglia, F.; Humphries, S. E.; Rauramaa, R.; de Faire, U.; Smit, A. J.; Giral, P.; et al.
Abstract: Background: Ischaemic stroke and coronary heart disease are important contributors to the global disease burden and share atherosclerosis as the main underlying cause. Recent evidence from a genome‐wide association study (GWAS) suggested that single nucleotide polymorphisms (SNP) near the MMP12 gene at chromosome 11q22.3 were associated with large‐vessel ischaemic stroke. Here, we evaluated and extended these results by examining the relationship between MMP12 and atherosclerosis in clinical and experimental studies. Methods and Results: Plasma concentrations of MMP12 were measured at baseline in 3394 subjects with high‐risk for cardiovascular disease (CVD) using the Olink ProSeek CVD I array. The plasma MMP12 concentration showed association with incident cardiovascular and cerebrovascular events (130 and 67 events, respectively, over 36 months) and carotid intima‐media thickness progression ( P = 3.6 × 10 −5 ). A GWAS of plasma MMP12 concentrations revealed that SNPs rs499459, rs613084 and rs1892971 at chr11q22.3 were independently associated with plasma MMP12 ( P < 5 × 10 −8 ). The lead SNPs showed associations with mRNA levels of MMP12 and adjacent MMPs in atherosclerotic plaques. MMP12 transcriptomic and proteomic levels were strongly significantly increased in carotid plaques compared with control arterial tissue and in plaques from symptomatic versus asymptomatic patients. By combining immunohistochemistry and proximity ligation assay, we demonstrated that MMP12 localizes to CD68 + macrophages and interacts with elastin in plaques. MMP12 silencing in human THP‐1‐derived macrophages resulted in reduced macrophage migration. Conclusions: Our study supports the notion that MMP12 is implicated in large‐artery atherosclerotic stroke, functionally by enhancing elastin degradation and macrophage invasion in plaques.